Hidden sector effects on double Higgs production near threshold at the LHC - Oliveira, A. C. A. [UNESP]; Rosenfeld, Rogério [UNESP] (Elsevier B.V., 2011)
In this Letter we study a novel effect of a hidden sector coupling to the standard model Higgs boson: an enhancement of the Higgs pair production cross section near threshold due to bound state effects. After summing the ladder contributions of the hidden sector to the effective ggHH coupling, we find the amplitude for gluon-gluon scattering via a Higgs loop. We relate this amplitude to the double Higgs production cross section via the optical theorem. We find that enhancements of the O(100) for the partonic cross section near the threshold region can be obtained for a hidden sector strongly coupled to the Higgs boson. The corresponding cross section at the LHC can be as large as O(10) times the SM result for extreme values of the coupling. The detection of such an effect could in principle lead to important information about the hidden sector. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Higgs boson; Bound states